Development of a Prototype for Water Reservoir Level Monitoring Using an ESP32 Board (International Journal of Geoscience, Engineering and Technology, 2024)
The ESP32 is a microcontroller developed by Espressif Systems. It is highly integrated with Wi-Fi and Bluetooth connectivity and widely used in Internet of Things (IoT) projects due to its versatility, performance, and low cost. It is employed in various sectors such as irrigation, commerce, and industry. Nowadays, water monitoring and efficient management are of great importance, mainly due to increased consumption and climate change. Based on this premise, a prototype was developed capable of remotely monitoring the water levels in domestic reservoirs via the Internet. With the development of the prototype, it was observed that it can positively improve, at a reduced cost, the processes of management and decision-making regarding residential water supply, contributing to the reduction of water waste.
Keywords: ESP32; Monitoring, Supply; Water level